The Rhetorical Style of Discussion Section of Research Articles Published in High-Impact Reputable Journals by Indonesian Authors in Different Fields - Safnil, Safnil; Maisarah, Ira; Pratami, Arleka (EDULIA: English Education, Linguistic and Art Journal, 2024)
This thesis aims to describe the rhetorical style of discussion section in 30 research articles (RAs) in six different fields of study, which those were written by Indonesian authors and successfully published in highly reputable journals. The fields comprised social sciences, language, engineering, physics, chemistry, and computer science. The research was designed as a mixed study, both quantitative and qualitative, as well as content analysis. One of the used instruments was a table containing eight textual moves model in the discussion sessions found by Swales. However, analysis focus was limited to Move 1 to Move 6. Data formed numbers and percentages indicating the amount of stages involved in all of the chosen RAs. Data were also in the form of extracts (authors’ arguments) which showed the moves applied in their articles. The results exhibited that there was a varied use of rhetorical style on each RAs, but Move 5 was used in all selected RAs (100%) which proved that the discussion section required a profound elaboration of the obtained research results. Besides, there were 27 RAs (90%) involved Move 3 as the second most used move which contained arguments about the research results. The writing patterns were also considered varied. The RAs of language and social sciences owned tendency to address more moves, while physics, chemistry, engineering, and computer science even just applied 2 moves. In accordance with the results, the use of moves highly depended on certain study fields and features of used data. Different disciplines tended had dissimilar rhetorical structures. The findings proved that the rhetorical style in the content of articles published in high-reputation journals were diverse, so as producing acceptable RAs for being published in high-reputation journals does not necessitate to involve all moves. Nevertheless, Move 5 must be presented in each of RAs to explain the results of research. Key Words: Eight Textual Moves, Research Article, Rhetorical Style